A simulation of controller system for home lighting and temperature devices / Abdul Rahman Mat Jusoh - Mat Jusoh, Abdul Rahman (Faculty of Information Technology and Quantitative Sciences, 2007)
The main purpose of this project is to build a Simulation of Controller System for Lighting and Temperature Device at home. Printer Parallel port will be modified and use in order to connect the host computer with the prototype circuit. Basically this system can be access locally via host PC and remotely through Internet Users can control their home lighting and temperature electrical devices remotely as long as there is a line connection through the mtemet. Users of this controller system will be able to set up their lighting and air-condition device based on timer. This project used LEDs and Electronic Fan Kit as a prototype for lighting and air-conditioner components. The application and circuit was built in other to complete this project.